Spondylodiscitis due to Parvimonas micra diagnosed by the melting temperature mapping method: a case report - Higashi, Yoshitsugu (BMC Infect Dis, 2017)
BACKGROUND: It has been suggested that more than 100 bacterial species can be identified using only seven universal bacterial primer sets in the melting temperature (Tm) mapping method and that these findings can be obtained within 3 h of sterile site collection. CASE PRESENTATION: A 67-year-old Japanese man with type 2 diabetes visited our hospital complaining of progressive lower back pain for 2 months. The patient was suspected to have spondylodiscitis on magnetic resonance imaging of the spine. Blood culture and transcutaneous vertebral biopsy were subsequently performed. Using the Tm mapping method, Parvimonas micra was detected from a transcutaneous vertebral biopsy specimen in 3 h. Gram-positive cocci were also detected by Gram staining and P. micra was identified directly from the anaerobic blood culture by matrix-assisted laser desorption ionization-time of flight mass spectrometry. Four days after admission, the biopsy specimen culture isolate was identified as P. micra. CONCLUSIONS: The Tm mapping method may be useful for the diagnosis of bacterial infections where diagnosis is challenging because of the difficulty of culturing.